Critiquing a Qualitative Study Using Tracy’s Big-tent Criteria - Saud saif Albusaidi (Research in Social Sciences and Technology- OpenED Network, 2019)
This paper critiques an article, which sheds light on the internationalisation of the curriculum. When classified within the main Western paradigms: positivism, interpretivism, critical theory and postmodernism, her article can be within the interpretivism. These paradigms are highlighted in this paper to engage the reader in critical reflection and to emphasise the differences between these paradigms. Big-tent markers, which are applied to evaluate the quality of qualitative research, are then critically implemented to highlight the strengths and weaknesses of that article in line with providing relevant suggestions.